IC 9405 Response Of Springs To Longwall Coal Mining At The Deer Creek And Cottonwood Mines Wasatch Plateau, Ut - Liane L. M. Kadnuck (The National Institute for Occupational Safety and Health (NIOSH), 1994)
This report summarizes the results of a hydrologic research study conducted by the U.S. Bureau of Mines (USBM) in cooperation with Energy West Mining Co. at the Deer Creek and Cottonwood Mines, near Orangeville, UT. The USBM evaluated hydrologic and overburden failure data to assess the response of local ground water to underground coal mining in single-and multiple-seam conditions. Fourteen springs located over the two mines were investigated in the study along with overburden failure response caused by longwall panel extraction. Spring discharge was compared to climatic variation and time of undermining to quantify response to undermining. Spring discharge had been reduced owing to below-normal precipitation during the period evaluated. The response of springs to mining in the vicinity was influenced in part by the thick overburden present at the study site the presence of hydrophilic clays and mudstones in the overburden stratigraphy, and elevation of the springs above mine level, which buffered the effects of undermining.